Bioinspired Photonic Ionogels as Interactively Visual Ionic Skin with Optical and Electrical Synergy. Issue 41 (12th September 2021) - Lyu, Quanqian; Wang, Shanzhen; Peng, Bolun; Chen, Xiaodong; Du, Shuo; Li, Miaomiao; Zhang, Lianbin; Zhu, Jintao
Abstract: With the ever‐growing demands for flexible smart interactive electronics, it remains highly desirable yet challenging to design and fabricate interactive ionic skin with multiple signal synergistic outputs. Herein, high‐performance photonic ionogels (PIGs) with excellent stability and synergy sensitivity are designed by locking a non‐volatile and non‐hygroscopic ionic liquid (IL), that is, 1‐ethyl‐3‐methylimidazolium bis‐(trifluoromethylsulfonyl)imide ([EMIm][TFSI]), into photonic elastomers based on polymer networks of poly(ethylene glycol) phenyl ether acrylate (PEGPEA). Through manipulating the degree of crosslinking, PIGs exhibit high sensitivity that can output distinct and intuitive color change in visual with the mechanochromic sensitivity of ≈1.76 nm per percent strain and clear electrical signal with the gauge factor of 1, in response to a tiny stretch of millimeter scale. Thanks to the stable photonic elastomers and IL employed, the PIGs developed in this study exhibit good performance under harsh and complex environmental conditions, including high/low temperature (from −35 °C to 100 °C), dry/wet air, and high vacuum. This study provides a novel strategy for developing integrated, stable, and multifunctional photonic ionogels for ionic skin sensors and flexible interactive devices with synergistically optical and electrical output. Abstract : Photonic ionogels with optical and electrical synergy inspired by chameleon skin are achieved by the combination of photonic elastomers and a non‐hygroscopic ionic liquid through hydrogen bonding. The photonic ionogels exhibit excellent stability and high sensitivity and are applied to high‐performance interactive visual ionic skins.